2022
DOI: 10.1007/s00402-022-04408-2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial tunnel enlargement is affected by the tunnel diameter-screw ratio in tibial hybrid fixation for hamstring ACL reconstruction

Abstract: Introduction There is no evidence on screw diameter with regards to tunnel size in anterior cruciate ligament reconstruction (ACLR) using hybrid fixation devices. The hypothesis was that an undersized tunnel coverage by the tibial screw leads to subsequent tunnel enlargement in ACLR in hybrid fixation technique. Methods In a retrospective case series, radiographs and clinical scores of 103 patients who underwent primary hamstring tendon ACLR with a hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…A large tunnel enlargement is associated with challenging revision surgery [9, 26]. However, the relationship between tunnel widening and postoperative knee laxity is still controversial [7, 11, 12]. In our study, increased femoral tunnel width correlated with increased STSD.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A large tunnel enlargement is associated with challenging revision surgery [9, 26]. However, the relationship between tunnel widening and postoperative knee laxity is still controversial [7, 11, 12]. In our study, increased femoral tunnel width correlated with increased STSD.…”
Section: Discussionsupporting
confidence: 48%
“…Theoretically, tunnel widening may be associated with delayed graft incorporation and resultant knee laxity [12, 24]. However, in clinical studies, it is still controversial whether tunnel widening affects postoperative results, including knee stability [7, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed preoperative planning, including MRI measurements, leads to the best outcome for the patient [ 7 , 15 , 35 ]. The hamstring tendons as well as the patella tendon are the most discussed autografts in the literature [ 12 , 25 , 31 ]. While the quadriceps tendon is mostly used for revision surgeries, it gains more and more popularity even for primary reconstructions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the precise causes of tunnel enlargement are very partially understood, it is generally agreed upon that multiple factors, including biological, biomechanical, and mechanical, contribute to its occurrence. Several studies reported which factors affect tunnel widening, such as the types of grafts, the type of fixation device, the position and size of the tunnel holes, the micro-motion of the graft in the tunnel, and altered cytokine levels in the synovial joint fluid [ 28 , 29 , 30 , 31 , 32 , 33 ]. Biological factors such as graft healing at the tunnel surface, inflammatory reactions, abnormal activity of the osteoclast, and infection are implicated in tunnel widening after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%